Exploring the Influence of Safety Perception and Safety Control on Clinical Performance Ability and Self Confidence in Patient Safety in Korean Nursing Students (Medico Legal Update, 2019)
Background/Objectives: This study aims to explore the effect of increased awareness of safety perception and safety control in providing self confidence in patient safety and clinical trials for Korean nursing students.Method/Statistical Analysis: The data were gathered using several questionnaires that were surveyed by 309 students located in C,I,J cities who gaved their permission to participate in this study. To identify the correlations among clinical performance ability, self confidence in patient safety, safety perception and safety control, SPSS 20.0 correlation program was used. We applied descriptive statistics, which include t-test, analysis of variance(ANOVA_Scheffe), Pearson’s correlation coefficient analysis, and multiple-regression analysis.Findings: There was a statistically significant positive correlation among safety perception, safety control, self confidence in patient safety and clinical performance ability. The regression model explained approximately 54.0% of self confidence in patient safety. Meanwhile, safety perception(p